Chinese manufacturing industry development strategy from the financial perspective: Grey modeling and analysis of data from the listing corporation China pharmaceutical manufacturing enterprises. Issue 2 (1st August 2016) - Pan, Yuxiang; Huang, Yimin; Qi, Ershi
Abstract : Purpose: – Based on literature review, the purpose of this paper is to design a comprehensive evaluation system for pharmaceutical industry from the financial perspective, and then analyses the development strategy of Chinese pharmaceutical industry according to the data of listed companies. Design/methodology/approach: – This paper analyses the development strategy of Chinese pharmaceutical industry through building the grey dominance evaluation model including absolute degree of grey incidence model and relative degree of grey incidence model. Findings: – Through the analysis of the grey dominance evaluation model, the authors find that four factors including total assets turnover, quick ratio, inventory turnover and current ratio can be grouped into first grade assessment indicator when evaluating the performance of Chinese pharmaceutical industry. These four indexes contain the concept of operational efficiency which shows that operation capability is the key to support the development of Chinese pharmaceutical industry, needing to be highly valued when organizations making business policy. When it comes to velocity of development, the contribution of R & D intensity is relatively small, which shows innovation ability of China's pharmaceutical industry is still weak. Innovation is the lifeblood of enterprise development, needing to be improved to promote enterprise's core competitiveness in the future development. Originality/value: – This paper selects Y1-Y7 as the performance evaluation system of pharmaceutical manufacturing enterprises, while X1-X15 as performance evaluation index system from the financial perspective, which indicated that the evaluation system is scientific and practical. The empirical result shows that the operation capability makes the largest contribution to the performance of China's pharmaceutical industry, while R & D ability and the enterprise core competitive ability are weak.